Singing Method: Easily Memorize Arabic Vocabulary and Mahfudzat - Andini Adia Putri MD; Mahdalia Zahra; Putri Wahyu Octavia Ningrum; Imam Tabroni (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research is motivated by children who tend to have difficulty memorizing. This study aims to determine the effect of the singing method on the ability to memorize vocabulary and mahfudzat at MDTA Al-Maghfirah Subang. This research was carried out in Subang, precisely at MDTA Al-Maghfirah. The sample used was 25 students in the Ibtida class or grade 1 elementary school. In this study, the singing method was used, which taught students using chanted vocabulary. This is evidenced by changes in the memorization rate of Al-Maghfirah MDTA students increasing rapidly and the results are good. Thus it can be concluded that the ability to memorize vocabulary and mahfudzat at MDTA Al-Maghfirah through the singing method has an effect on the ease of memorizing. The results of this study are expected to be useful for teachers and others